Diversity and Abundance of Ice Nucleating Strains of Pseudomonas syringae in a Freshwater Lake in Virginia, USA - Pietsch, Renée B.; Vinatzer, Boris A.; Schmale, David G. (Frontiers in Microbiology, 2017)
The bacterium Pseudomonas syringae is found in a variety of terrestrial and aquatic environments. Some strains of P. syringae express an ice nucleation protein (hereafter referred to as Ice+) allowing them to catalyze the heterogeneous freezing of water. Though P. syringae has been sampled intensively from freshwater sources in France, little is known about the genetic diversity of P. syringae in natural aquatic habitats in North America. We collected samples of freshwater from three different depths in Claytor Lake, Virginia, USA between November 2015 and June 2016. Samples were plated on non-selective medium (TSA) and on medium selective for P. syringae (KBC) and closely related species to estimate the total number of culturable bacteria and of P. syringae, respectively. A droplet freezing assay was used to screen colonies for the Ice+ phenotype. Ice+ colonies were then molecularly identified based on the cts (citrate synthase) gene and the 16S rDNA gene. Phylogenetic analysis of cts sequences showed a surprising diversity of phylogenetic subgroups of P. syringae. Frequencies of Ice+ isolates on P. syringae selective medium ranged from 0 to 15% per sample with the highest frequency being found in spring. Our work shows that freshwater lakes can be a significant reservoir of Ice+ P. syringae. Future work is needed to determine the contribution of P. syringae from freshwater lakes to the P. syringae populations present in the atmosphere and on plants and, in particular, if freshwater lakes could be an inoculum source of P. syringae-caused plant disease outbreaks.